Plan estratégico para una empresa de tecnología orientada a entregar bienes y servicios de comunicaciones unificadas y seguridad de la información - Yerovi Arias, René Javier (2014)
This paper defines a strategic plan for the technology department of a company whose line of business is in the sales and implementation of technology goods and services, which is why the strategic plan covers the entire company in general. The methodology used to prepare this document is IBM-BSP/SA which is a tool to achieve the goal of optimizing processes for obtaining greater performance with lower costs; this is achieved by merging techniques to manage information through administrative tools to meet the objectives of the organization...